New high-rate wireless LAN standards. - Van Nee, R. (IEEE Communications magazine)
After the IEEE 802.11 standardization group established the first wireless LAN, several efforts were started to increase data rates and also to use other bands. This article describes the new wireless LAN standards developed by IEEE 802.11, ETSI BRAN, and MMAC. The new standards are targeting data rates up to 11 Mb/s in the 2.4 GHz band and up to 54 Mb/s in the 5 GHz band